The Influence of Organizational Culture and Motivation on Teacher Performance at SMK Nusa Bangsa, Jampang Parung, Kemang, Bogor Regency - Putra, Mulyana Gustira (Majalah Ilmiah Bijak, 2024)
The purpose of this research is to determine the influence of organizational culture and motivation on teacher performance at SMK Nusa Bangsa Jampang Parung Kemang, Bogor Regency. The type of research used is quantitative descriptive with multiple linear regression methods as the dependent variable is performance while the independent variables are organizational culture and motivation. Saturated sampling was 25 teachers at SMK Nusa Bangsa. The research results show that organizational culture and motivation simultaneously have a positive and significant effect on teacher performance, partially both organizational culture and motivation together have a positive and significant effect on teacher performance at Nusa Bangsa Parung Kemang Vocational School, Bogor Regency.